Caffeine in Prepackaged Tea Leaves: A Food Labelling Concern. - Cheng, R.; Wong, Chun-Keung; Man, Hok-Leung (2014)
Being the second most consumed drink after water and more than coffee, chocolate, soft drinks, and alcohol all combined1, tea is not only a popular drink but there are also many well-being claims2 like aiding in digestion, controlling of weight, relieving stress, and even strengthening our minds and physical capacities. Caffeine in teas, when consumed at moderate levels, likewise, contributes to some favorable cognitive and mood effects in humans too yet it has also been postulated to be associated with various negative reproductive issues, such as miscarriages, premature births, low birthweights, and extensive research, however, inconclusive is still being conducted between caffeine consumption and cardiovascular disease and osteoporosis9. This paper aims to determine the caffeine content of prepackaged brands of tea leaves available in the market via the HPLC-PDA method. Prepackaged tea leaves including white, black, oolong, green and pu-erh were examined. Using the Agilent TC-C18 column, caffeine contents in the tea leaves were studied via reversed-phase HPLC with a wavelength setting of 280 nm. Samples were isocratically eluted with a mobile phase consisting of 1% acetic acid and acetonitrile in the ratio of 8:2 with a flow rate of 1.0mL/min. Extraction of caffeine in boiling water was performed to mimic the real-life situation of tea drinking. The results provided innovative insights toward the future development of food composition and labeling regulation on prepackaged tea leaves, particularly in Asia where China, India, Russia and Japan alone have already accounted for some 50% of the world’s tea consumption.